Analysis of Problem of Perceiving and Understanding Literary Texts by Philology Students - Інна Хижняк; Назар Ляшов (Психолінгвістика, 2019)
Introduction. The article discloses the importance of conducting psycholinguistic analysis of perceiving and understanding voluminous literary texts by philology students; the issue is relevant as there is a lack of research that concerns revealing the essential aspects of these processes, as well as the influence of conducting psycholinguistic analysis on effective performance in philology students’ professional activities is highlighted. The goal of the article is to conduct a theoretical analysis of the problem of perceiving and understanding literary texts by philology students and identify the level of development of future teachers of language and literature individual practical skills on decoding the content of a large prose fictional text.